A system for artificial light signal transduction via molecular translocation in a lipid membrane. Issue 8 (11th February 2022) - Yang, Huiting; Du, Shengjie; Ye, Zhicheng; Wang, Xuebin; Yan, Zexin; Lian, Cheng; Bao, Chunyan; Zhu, Linyong
Abstract : Photoisomerization chemistry was used to simulate light signal transduction, in which the light-controlled reciprocating translocation of molecules in lipids activates or deactivates the hydrolysis reaction for an encapsulated substrate. Abstract : Light signal transduction pathways are the central components of mechanisms that regulate plant development, in which photoreceptors receive light and participate in light signal transduction. Chemical systems can be designed to mimic these biological processes that have potential applications in smart sensing, drug delivery and synthetic biology. Here, we synthesized a series of simple photoresponsive molecules for use as photoreceptors in artificial light signal transduction. The hydrophobic structures of these molecules facilitate their insertion into vesicular lipid bilayers, and reversible photoisomerization initiates the reciprocating translocation of molecules in the membrane, thus activating or deactivating the hydrolysis reaction of a precatalyst in the transducer for an encapsulated substrate, resulting in a light controllable output signal. This study represents the first example of using simplified synthetic molecules to simulate light signal transduction performed by complex biomolecules.